Neutrophil Myeloperoxidase Index in Dogs With Babesiosis Caused by Babesia rossi - Celliers, Anri; Rautenbach, Yolandi; Hooijberg, Emma; Christopher, Mary; Goddard, Amelia (Frontiers in Veterinary Science, 2020)
Babesiosis caused by the virulent tick-borne hemoprotozoan, Babesia rossi, results in a marked systemic inflammatory host response in dogs. Neutrophils form part of the innate immune response and contains myeloperoxidase (MPO) as the predominant component of the neutrophil lysosomal protein in azurophilic granules. The neutrophil myeloperoxidase index (MPXI), determined on the ADVIA hematology analyzer, is a quantitative estimate of intracellular MPO content. Objectives of this study were to: (a) compare MPXI in dogs with babesiosis with healthy control dogs; (b) compare MPXI in dogs that died from babesiosis with dogs that survived and controls; and (c) correlate the MPXI with the previously determined segmented and band neutrophil count and cytokine concentrations in dogs with babesiosis. Data for 140 dogs naturally infected with B. rossi and 20 healthy control dogs were retrospectively evaluated. Neutrophil counts and MPXI were determined on an ADVIA 2120 analyzer. Cytokine concentrations (interleukin (IL)-2, IL-6, IL-8, IL-10, IL-18, granulocyte-macrophage colony stimulating factor (GM-CSF), and monocyte chemo-attractant protein-1 (MCP-1)) were determined using a canine-specific multiplex immunoassay. The mortality rate of the Babesia-infected dogs was 11% (15/140). MPXI was significantly higher in Babesia-infected dogs (P = 0.033), and in Babesia-infected non-survivors (P = 0.011), compared with healthy control dogs. In Babesia-infected dogs a significant positive correlation was found between MPXI and IL-10 (r = 0.211, P = 0.039) and a significant negative correlation was found between MPXI and IL-8 (r = -0.350, P < 0.001). In Babesia-infected non-survivors, significant positive correlations were found between MPXI and IL-2 (r = 0.616, P = 0.033), IL-6 (r = 0.615, P = 0.033), IL-18 (r = 0.613, P = 0.034), GM-CSF (r = 0.630, P = 0.028) and MCP-1 (r = 0.713, P = 0.009). In Babesia-infected survivors, a significant negative correlation was found between MPXI and IL-8 (r = -0.363, P = 0.001). MPXI was correlated with pro-inflammatory cytokines in Babesia-infected dogs that died. The potential of MPXI as a novel marker of inflammation and prognosis in dogs infected with B. rossi, thus warrants further investigation.